The Implementation of Application-Based Learning Media Canva in Increasing Students' Interest of Class VIII Christian Religious Learning at Marisi Medan Private Middle School - Siringoringo, Widi L.; Munthe, Bangun; Bangun, Bangun (International Journal on Advanced Science, Education, and Religion, 2024)
The purpose of this research is to see how the implementation of learning media based on the Canva application increases students' interest in learning in Christian religious learning in Class VIII SMP Marisi Medan with a total of 26 people. This research uses a descriptive method, while the data analysis carried out by hypothesis research is product moment person correlation and the data collection tool is a questionnaire. From the test results, a correlation (r) of 0.63 was obtained with a determination test of 39.69% and to determine whether the correlation coefficient was significant at the real level (a) = 0.05 then a "t" test was conducted with the testing criteria if tcount obtained from the calculation is greater (>) than ttable at a significance level of 1-0.05 with dk= n – 2 then the hypothesis is accepted and in other cases it is rejected. From the test results obtained tcount > ttable (3.98 > 1.71), then the hypothesis is accepted. Thus, a significant relationship can be found between the implementation of learning media based on the Canva application in increasing students' interest in learning in class VIII Christian religious education subjects at Marisi Medan Private Middle School. Keywords: Canva Learning Media, Learning Interests, Canva Learning Media, Learning Interests